The Cosmological History of Accretion onto Dark Halos and Supermassive Black Holes - Miller, L; Percival, W; Croom, S; Babic, A (2006)
Aims: We investigate the cosmological growth of dark halos and follow the consequences of coeval growth for the accretion history of associated supermassive black holes. Methods: The Press-Schechter approximation is used to obtain an analytic expression for the mean rate of growth of dark matter halos. Dark halo accretion rates are compared with numerical work and the consequences for understanding AGN evolution are described. Results: The mean accretion rate onto dark matter halos is shown to have a simple analytic form that agrees with previous numerical work and that may easily be calculated for a wide range of halo mass, redshift and cosmological parameters. The result offers a significant improvement over published fitting formulae deduced from merger trees. We then consider the growth of associated supermassive black holes, and make a basic test of the simple hypothesis of `Pure Coeval Evolution' (PCE) in which, on average, black hole growth tracks dark halo growth. We demonstrate that both the absolute value of the integrated AGN bolometric luminosity density and its cosmological evolution derived from hard X-ray surveys are well-reproduced by PCE. Excellent agreement is found at z >~ 0.5, although the observed luminosity density drops by a factor 2 compared with PCE by z=0: black hole growth appears to decouple from halo growth at low redshifts, and this may be related to the phenomenon of `cosmic downsizing'. Overall, AGN evolution appears either to be caused by or to be closely linked to the slow-down in the growth of cosmic structure. We also discuss the mean Eddington ratio averaged over all galaxies, which is predicted to show strong evolution to higher values with redshift.